2022
DOI: 10.1371/journal.pone.0268839
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery in 1 minute after the 6-minute walk test predicts adverse outcomes in pulmonary arterial hypertension

Abstract: Heart rate recovery in 1 minute (HRR1) after the end of the 6-minute walk test (6MWT) is a non-invasive method of determining autonomic dysfunction. This parameter remains largely unexplored in pulmonary arterial hypertension (PAH) registries. We aimed to define the cut-off value and accuracy for abnormal HRR1 after the 6MWT and to investigate the association between HRR1 and clinical worsening in patients with PAH. This composite outcome was defined as first occurrence of all-cause death OR hospitalization fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The SBPR decreases after exercise may be a reflection of a person's level of physical activity and fitness. The more rapid decline indicates the higher level of physical fitness, and a greater decrease in SBP from peak exercise to the recovery may reflect good aerobic capacity [16,23,35]. Researches also showed age differences in SBPR after exercise with faster recovery of SBP in younger adults than older group [36].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The SBPR decreases after exercise may be a reflection of a person's level of physical activity and fitness. The more rapid decline indicates the higher level of physical fitness, and a greater decrease in SBP from peak exercise to the recovery may reflect good aerobic capacity [16,23,35]. Researches also showed age differences in SBPR after exercise with faster recovery of SBP in younger adults than older group [36].…”
Section: Discussionmentioning
confidence: 93%
“…Blunted HRR has been reported the association with chronic heart failure and new-onset atrial fibrillation [9,10]. It has been revealed as an independent predictor of mortality and adverse outcomes [11][12][13][14][15][16][17][18]. Mahfouz et al [19], suggested that abnormal HRR and delayed systolic blood pressure recovery after exercise were correlated with impaired endothelial function and diastolic dysfunction in prediabetics.…”
Section: Introductionmentioning
confidence: 99%
“…The SBPR decreases after exercise may be a reflection of a person’s level of physical activity and fitness. The more rapid decline indicates the higher level of physical fitness, and a greater decrease in SBP from peak exercise to the recovery may reflect good aerobic capacity [ 16 , 23 , 27 ]. Researches also showed age differences in SBPR after exercise with faster recovery of SBP in younger adults than older group [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blunted HRR has been reported the association with chronic heart failure and new-onset atrial fibrillation [9,10]. It has been revealed as an independent predictor of mortality and adverse outcomes [11][12][13][14][15][16][17][18]. Mahfouz et al [19], suggested that abnormal HRR and delayed systolic blood pressure recovery after exercise were correlated with impaired endothelial function and diastolic dysfunction in prediabetics.…”
Section: Introductionmentioning
confidence: 99%